Pengukuran Kualitas Aplikasi PeduliLindungi Dengan Metode WebQual 4.0 - Alfarisi, Tri Lukman; Khubaero, Ulfi; Effendi, Lasman (Jurnal Keilmuan Teknologi Informasi dan Ilmu Manajemen (Justifi), 2022)
During the current Covid-19 pandemic, almost all activities have been shifted online to break the chain of transmission of the virus. To help the government detect the transmission of Covid-19, the Indonesian Ministry of SOEs together with the Indonesian Ministry of Communication and Information and Telkom Indonesia initiated the creation of the PeduliLindungi application. This application still has problems for its users. The purpose of this study was to determine the quality of the PeduliLindungi application. The method used is WebQual 4.0 by using 3 variables, namely usability, information quality and interaction quality, as well as descriptive analysis to determine the criteria for the data obtained. The results showed that the usability variable got very good criteria, then the information quality variable also got very good criteria and finally the interaction quality variable got good criteria.